2010
DOI: 10.1007/s00439-010-0883-7
|View full text |Cite
|
Sign up to set email alerts
|

FTO influences on longitudinal BMI over childhood and adulthood and modulation on relationship between birth weight and longitudinal BMI

Abstract: SNP rs9939609 within the fat mass and obesity associated gene (FTO) is strongly associated with adult body mass index (BMI). However, influences of FTO on longitudinal BMI change from childhood to adulthood have not been examined. Knowledge is limited on FTO, modulating the association between birth weight and longitudinal change of BMI. This longitudinal study examined SNPs of FTO in 658 white subjects from childhood (3-17 years) to adulthood (18-45 years). No significant associations of FTO SNPs with either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…This single-nucleotide polymorphism is located in the first intron of the FTO gene at a position of 52.38 Mbp, where sequence is strongly conserved across species [19]. Several studies demonstrated that A allele carriers of rs9939609 have a higher body weight than carriers homozygous for the wild-type T allele [20,21], as indicated by our results.…”
Section: Discussionsupporting
confidence: 63%
“…This single-nucleotide polymorphism is located in the first intron of the FTO gene at a position of 52.38 Mbp, where sequence is strongly conserved across species [19]. Several studies demonstrated that A allele carriers of rs9939609 have a higher body weight than carriers homozygous for the wild-type T allele [20,21], as indicated by our results.…”
Section: Discussionsupporting
confidence: 63%
“…We previously confirmed that FTO tag SNPs, including rs9939609, were associated with longitudinal adulthood BMI [12]. In this study, we extended the test to 23 additional GWAS-significant SNPs that were genotyped in the Bogalusa Heart Study cohort.…”
Section: Discussionmentioning
confidence: 54%
“…However, no previous study provided the kind of direct evidence for an association between FTO and birth weight that was observed in this study. The FTO candidate SNPs (rs6499640, rs1121980, and rs8050136) were located at the 5′ end, upstream of the tag SNPs (rs9939609, rs17820875, and rs860713) that were explored previously [12] (Figure 2). These findings indicate that different regions of FTO are involved in childhood and adulthood obesity development; the upstream variant (rs6499640) was found to influence childhood BMI, and the downstream variants (rs1121980, rs8050136, rs9939609 [12], rs17820875 [12], and rs860713 [12]) were found to influence adulthood BMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations